PERAN PEREMPUAN DALAM UPACARA KENDURI SKO PADA MASYARAKAT KERINCI - Sean Popo Hardi; Mohd. Norma Sampoerno; Maratun Saadah (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2021)
Kerinci is one of the regions in Sumatra with a strong matrilineal culture. This is reflected in the customs that place the role of women more dominant than men as contained in kenduri Sko ceremony activities. This research aims to see how the role of women contained in the traditional ceremony of Kenduri Sko. This study is a qualitative descriptive study that seeks to explain the representation of matrilineal culture through the role of women in the indigenous upara Kenduri Sko. The results showed that the dominance of women in the largest ceremony for Kerinci society, Kenduri Sko, was very dominant. It is seen from the role of women as dayangs in the series of "mendingin" rituals, women also become the main actors in the "iyo-iyo" dance. Women become parapatoh presenters to recall the heirlooms of ancestors who became the main purpose of the Kenduri Sko ceremony.